2014
DOI: 10.1111/jdv.12467
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of antifungal PACT in an in vitro model of onychomycosis

Abstract: PACT appears to be an effective treatment of onychomycosis in vitro. The promising results need to be validated by clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…The promising results encouraged researchers to apply the 3 formulation in a patient with confirmed onychomycosis. The use of three PACT sessions over the week led to a significant improvement in nail morphology, confirmed in a 6-month follow-up [62]. The effectiveness of PACT and cyclopiroxolamine against T. rubrum dermatophytes was also experimentally compared.…”
Section: Toluidine Blue O and New Toluidine Blue Omentioning
confidence: 80%
See 1 more Smart Citation
“…The promising results encouraged researchers to apply the 3 formulation in a patient with confirmed onychomycosis. The use of three PACT sessions over the week led to a significant improvement in nail morphology, confirmed in a 6-month follow-up [62]. The effectiveness of PACT and cyclopiroxolamine against T. rubrum dermatophytes was also experimentally compared.…”
Section: Toluidine Blue O and New Toluidine Blue Omentioning
confidence: 80%
“…After 60 s of incubation followed by 30 s irradiation, it turned out that this procedure was effective against each strain, and an increase in activity was observed with an increasing light dose (dose equal 24 J/cm 2 at the light-source power 400 mW) [61]. After initial in vitro tests against Trichopyton rubrum, 3 also found an application in the treatment of onychomycosis [62]. The use of PS in the in vitro model at a concentration of 20 µg/mL after 30 min irradiation with 200 J/cm 2 light led to complete eradication of fungi.…”
Section: Toluidine Blue O and New Toluidine Blue Omentioning
confidence: 96%
“…Mehra et al . ( 2015 ) demonstrated that TBO‐mediated aPDT effectively inhibited the growth of T. rubrum in onychomycosis ex vivo model. In line with these previous studies, the present study used healthy human nail pieces and microconidia of T. rubrum to establish tinea unguium ex vivo model and investigated the photodynamic treatment effect of AE for onychomycosis.…”
Section: Discussionmentioning
confidence: 99%
“…This study reports on one of our MFPSs designed for PDT of dermatophytic onychomycoses. With respect to the effectiveness of different onychomycosis treatment strategies, various models have been developed recently [ 19 , 20 , 21 ]. Although many of these models use a realistic topical drug application, they have done so on bovine hoof as a keratin source instead of human nail material [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nail penetration behavior, however, will also be affected by the presence of fungal growth. On the other hand, the model used by Mehra et al [ 19 ] included T. rubrum- infected human keratin but obtained this material from powdered nails. This implies that one of the onychomycosis treatment obstacles, the stiffness of the nail plate, cannot be tested in this model.…”
Section: Discussionmentioning
confidence: 99%